(3TQM GdCQLhRI GdjGSejfjI (B((3aj Yde GdLHQ hGdebGHdI(B)s - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s; (3YHO Gddg Hf eMeO Hf MLGL, CHh eMeO GdeYQha H` GHf GdjGSejf,J (B601 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI(B: (3GdMeO ddg GdPi LHQ bdhH ChdjGFg s
(3BNQgG (B:s
(3hai gPG GdbOQ GdPi ChQOJg caGjI ddeHJOF Ef TGA Gddg s
(3fXegG CHh eMeO YHOGddg Hf MLGL GdeYQha HGHf GdjGSejf GdeJhai fMh (B600 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdQjGVjGJs